Еnergy cooperation between the EU and Сentral Asia (International relations and international law Journal, 2017)
The article analyzes the relationship between the European Union and the Republic of Kazakhstan in the framework of the energy sector. Kazakhstan is a country with vast energy resources, therefore it is one of the most important players in this industry. The European Union, in turn, is a major consumer of energy in the eastern hemisphere. The energy dialogue is a key component of Kazakhstan’s cooperation with the EU. Relationships are being built in the framework of the Energy Charter Treaty and the support of programs such as TRACECA and INOGATE.
Keywords: the European Union; the Republic of Kazakhstan; Central Asia; energy resources; prospects for cooperation; The Energy Charter Treaty